2010
DOI: 10.1161/hypertensionaha.110.157271
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone Synthase Inhibition With LCI699

Abstract: Abstract-We report the first administration of an orally active aldosterone synthase inhibitor, LCI699, to 14 patients with primary aldosteronism. After a 2-week placebo run-in, patients received oral LCI699 (0.5 mg BID) for 2 weeks, LCI699 (1.0 mg BID) for 2 weeks, and placebo for 1 week. We assessed changes in hormone concentrations, plasma potassium levels, and 24-hour ambulatory systolic blood pressure and safety. The supine plasma aldosterone concentration decreased from 540 pmol/L (95% CI: 394 to 739 pmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(65 citation statements)
references
References 38 publications
1
64
0
Order By: Relevance
“…17 It was found that 7n provided selective reduction of plasma aldosterone levels without an effect on baseline morning cortisol levels. 15,16 However, suppression of stimulated cortisol levels was seen at doses above 0.5 mg, which can be attributed to the modest selectivity for CYP11B2 over CYP11B1.…”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 99%
See 1 more Smart Citation
“…17 It was found that 7n provided selective reduction of plasma aldosterone levels without an effect on baseline morning cortisol levels. 15,16 However, suppression of stimulated cortisol levels was seen at doses above 0.5 mg, which can be attributed to the modest selectivity for CYP11B2 over CYP11B1.…”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 99%
“…In human studies, treatment with 7n was well tolerated and effective in reducing aldosterone levels to provide sustained lowering of blood pressure in patients with primary aldosteronism, 15 primary hypertension, 16 and resistant hypertension. 17 It was found that 7n provided selective reduction of plasma aldosterone levels without an effect on baseline morning cortisol levels.…”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 99%
“…Moreover, the drug induced a blunted glucocorticoid response to ACTH of uncertain clinical significance. 81,82 …”
Section: Drug-based Treatment For Pamentioning
confidence: 99%
“…The initial reports of LCI699 explored its aldosterone synthase (CYP11B2) inhibitory action, at doses of up to 2 mg/d in patients with primary hyperaldosteronism and essential hypertension, and demonstrated correction of hypokalaemia and hypertension [63,64]. The induced hypoadrenalism precluded the use of this drug, but unleashed the development of clinical trials evaluating its efficacy and safety in the treatment of CD.…”
Section: Lci699mentioning
confidence: 99%